Individual Insurance and Mutual Support Arrangements in Developing Countries - Friederike Lenel (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Insurance coverage in the developing world is expanding rapidly. As recently as 2005, only a small number of commercial insurers offered insurance products that specifically targeted low-income people (`microinsurance'). Seven years later, in 2012, more than half of the world's 50 largest insurance companies were involved in microinsurance. International donor organizations, which identified the promotion of social protection systems as a key priority, strongly encourage this development. Yet, while the positive role insurance can play for poverty reduction is fairly uncontroversial, the potential negative side-effects of the rapid insurance expansion are less apparent. One concern is that the establishment of formal insurance schemes can lead to a paradigm shift: market-based schemes crowd-out social cohesion; adversely affecting the mutual support arrangements that form an important pillar of the risk management strategies of the poor. Evidence isnot clear-cut.
Keywords: 330